(untitled) (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Global references continue to suggest that, Information and Communication Technologies (ICTs) in healthcare service delivery has brought with it great advancements. In developing countries, various ICTs and healthcare initiatives/ policies have been put in place to address challenges of providing equitable health care and improving the quality of health care services in a cost efficient manner. Although in Africa the advent of e-health has offered an exciting opportunity to reduce or control the growing healthcare inequity, a lot still needs to be done in drawing up the appropriate strategies to narrow the disparities in the access to healthcare delivery information (Kifle and Mbarika, 2006). These disparities have led to the coinage of the term “health divide”, meaning the gap existing in the access to healthcare information using ICTs between those who have access to healthcare and those who do not have (Mbarika and Samake, 2005). South Africa has implemented initiatives addressing such disparities however; all has not been well with most of these initiatives as they have failed to achieve their anticipated objectives. This therefore, calls for effective e-health strategies to ensure the full exploitation of the benefits it brings towards narrowing of the health divide. This article therefore outlines the research question as: What are the effective strategies of narrowing the health divide in developing countries? Purpose: To identify those factors or variables imperative to drawing up strategies for narrowing the health divide using ICTs within the public healthcare sector in a developing country context, in this case South Africa. Research Methodology: Data was gathered using literature analysis, key informant interviews and government websites on health. Data analysis methods used on survey data include, descriptive statistics, correlation analysis, and factor analysis. Results: Exhausting all the variables towards narrowing the health divide is very complex. However, findings suggest that there is need to attend to socio-technical, economic, and political issues to address this problem. Issues noted were, the failure of the public sector to keep pace with the private sector technologically, poor funding, lack of policy makers, poor infrastructure, unskilled personnel amongst many other issues. Conclusion: Proper planning for ICT deployment can bear tremendous results in narrowing the health divide. However, there is need to engage a diverse group of health professionals and policy makers including the public.